Poland’s Energy Security in the Baltic Sea Region - Miłosz GAC; Ireneusz MICIUŁA; Henryk WOJTASZEK (Communications of International Proceedings, 2020)
Energy security plays an extremely important role in the creation of geopolitical concepts and strategies of contemporary states. The constantly increasing demand for energy determines the foreign policy of many international entities, which aim atensuring the continuity of supply at both the lowest possible price and the best quality, to enable the productive use of energy while respecting the natural environment. This thesis is confirmed by the Polish strategy of energy security, which focuses on particular activities such as: ensuring a real diversification, development of the transmission and distribution system and conducting an appropriate storing policy. The Baltic Sea region plays a key role in the Polish energy supply system by creating the possibility for diversification of the supply of strategic resources. Additionally, geographical characteristic of this areais also used to create the superpower policy of the Russian Federation, which uses rich deposits of strategic resources as an instrument of political game.
Keywords: Energy security; diversification; the Baltic Sea; LNG; Nord Stream.